Studi Pengendalian Banjir Sungai Balang Sikuyu Kabupaten Bantaeng - Fadhila, Febrianty; Badrun, Burhanuddin; Yusuf , Rumpang (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
Flooding is the process of river water overflowing onto land, which can lead to property damage and even loss of life. This study was conducted in Karatuang Village, Bantaeng Regency, aiming to analyze planned flood discharge and flood control for return periods of 2, 5, 10, 25, 50, and 100 years. The analysis used average rainfall data from two rainfall stations: Biangkeke and Pajujukang. Rainfall calculation applied the Log Pearson Type III and Gumbel methods, while frequency distribution suitability was tested with the Chi-Square and Kolmogorov-Smirnov tests. Based on the flood discharge analysis using the Nakayasu Synthetic Unit Hydrograph (HSS) method, results for each return period showed: 2 years at 51.84 m³/s, 5 years at 75.993 m³/s, 10 years at 91.184 m³/s, 25 years at 108.897 m³/s, 50 years at 124.613 m³/s, and 100 years at 138.745 m³/s. For a 2-hour duration, the calculated volume was 220,012 m³, while the check dam’s capacity of 24,750 m³ was insufficient for the 2-year return period. Thus, flood control measures include river normalization by widening and deepening the riverbed to increase capacity.